2018
DOI: 10.1158/1055-9965.epi-18-0480
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Participation in Human Papillomavirus Self-Sampling among Nonattenders to Cervical Cancer Screening in Denmark

Abstract: Offering human papillomavirus-based self-sampling to nonparticipants in routine cervical cancer screening can increase screening participation. However, little is known about characteristics of women who accept self-sampling. In this population-based study, we investigated determinants for participation in self-sampling among Danish nonattenders to routine cervical cancer screening. During 2014 to 2015, a random sample of screening nonparticipants ages 27 to 65 years living in the Capital Region of Denmark wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Furthermore, in line with our interaction results regarding the influence of native background on HPV vaccination and subsequent screening, two recent Danish studies showed both lower attendance and lower effect size of offering HPV self-sampling to non-native women than to native women,54,55 supporting that health-promoting behavior may be influenced by nativity/region of origin.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in line with our interaction results regarding the influence of native background on HPV vaccination and subsequent screening, two recent Danish studies showed both lower attendance and lower effect size of offering HPV self-sampling to non-native women than to native women,54,55 supporting that health-promoting behavior may be influenced by nativity/region of origin.…”
Section: Discussionsupporting
confidence: 89%
“…Sometimes women hesitate to participate in screening because of personal, practical, and financial reasons. 40 In conclusion, our study demonstrated that p16/ Ki-67 dual-stain test could achieve better performance compared with TCT examination for ≥CIN2 or ≥ CIN3 detection, representing a promising approach as a specific and efficient triage strategy for high-risk HPV-positive women.…”
Section: Discussionmentioning
confidence: 71%
“…All data were supplied by the laboratories, and women could not be tracked if they had moved to another screening provider. Sometimes women hesitate to participate in screening because of personal, practical, and financial reasons 40 …”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the attendance rates, the Dutch Health Council recently advised to send self-sampling kits to all women invited for cervical screening, since this opt-out approach is considered to be more effective compared to the currently used opt-in approach ( Arbyn et al, 2018 , Dutch Health Council, 2021 ). However, this effect might be limited in women with a lower socio-economic status, women with a migration background, or women who have not attended cervical cancer screening for over ten years, because they are less prone to accept cervicovaginal self-sampling than the general population ( Harder et al, 2018 ). Furthermore, less trust and low self-efficacy expectations towards performing correct cervicovaginal self-sampling might explain why only 5–8% of women attending cervical cancer screening participate by the option of cervicovaginal self-sampling ( Integraal Kankercentrum Nederland, 2021 , Polman et al, 2019 , Williams et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%